PENGARUH PROFITABILITAS, LEVERAGE DAN LIKUIDITAS TERHADAP PENGUNGKAPAN CORPORATE INTERNET REPORTING PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI TAHUN 2018 - 2020 - Judianto Tjahjo Nugroho (Sekolah Tinggi Ilmu Ekonomi Gici, 2021)
In this era of industrial resolution 4.0, many companies are competing to be the best in their respective fields. The impact of this pandemic turned out to be quite large felt by entrepreneurs, therefore entrepreneurs are faced with various choices to keep their companies operating and moving forward. Not only that, but companies are also required to be more transparent in disclosing information about their companies. A company's financial statements will have benefits if they are delivered accurately and on time to users for decision making. This reflects how important the timeliness of financial statements is presented to the public. The purpose of this study is to analyze the effect of profitability, leverage and liquidity on corporate internet reporting disclosure in banking companies listed on the IDX in 2018 – 2020. The population in this study is all banking companies listed on the IDX in 2018 - 2020. Samples were taken using purposive sampling techniques. Data collection techniques use secondary data. Data analysis methods using balanced panel regression analysis include t-test, F-test and coefficient of determination using Eviews. The results of the analysis show that all indicators used are valid and reliable. The regression equation obtained is CIR = 70.932 + 2.65E-25X1 + 1.61E-21X2 – 1.01E-25X3 + μ. Based on the t-test and F test, it was found that the variables of profitability, leverage and liquidity did not have a significant effect on the disclosure of corporate internet reporting in banking companies listed on the IDX in 2018 - 2020, either partially or simultaneously